2003
DOI: 10.1097/01.ccm.0000079819.27515.8e
|View full text |Cite
|
Sign up to set email alerts
|

Unmeasured anions in critically ill patients: Can they predict mortality?*

Abstract: Base excess, base excess caused by unmeasured anions, and anion gap are good predictors of hyperlactatemia (>5 mmol/L). Acid-base variables and, specifically, "unmeasured anions" (anion gap, anion gap corrected, base excess caused by unmeasured anions, strong ion gap), irrespective of the methods used to calculate them, are not accurate predictors of hospital mortality rate in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
108
3
13

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 28 publications
6
108
3
13
Order By: Relevance
“…Induction, time point of inducing anesthesia; weaning, 5 min after weaning from CPB; closure, time point of chest closure; UMA, unmeasured anions; Change in lactate induction-weaning, change in the lactate level from induction to CPB weaning; Change in lactate weaning-closure, change in the lactate level from CPB weaning to chest closure; Change in lactate induction-closure, change in the lactate level from induction to chest closure; Change in UMA induction-weaning, change in the UMA level from induction to CPB weaning; Change in UMA weaning-closure, change in the UMA level from CPB weaning to chest closure; Change in UMA induction-closure, change in the UMA level from induction to chest closure; AUC, area under curve; Pauc, P value of the comparison of AUCs between lactate and UMA at each time point. pediatric cardiac surgery in some studies (Durward et al 2005;Murray et al 2007), whereas other studies showed that the UMA level offers no additional advantage over the lactate level in predicting surgical outcomes (Cusack et al 2002;Hatherill et al 2003;Rocktaeschel et al 2003). Both of these reports focused on postoperative or critically ill patients in the ICU.…”
Section: Fig 3 Periopetraive Hemodynamic Variables In the Mae Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction, time point of inducing anesthesia; weaning, 5 min after weaning from CPB; closure, time point of chest closure; UMA, unmeasured anions; Change in lactate induction-weaning, change in the lactate level from induction to CPB weaning; Change in lactate weaning-closure, change in the lactate level from CPB weaning to chest closure; Change in lactate induction-closure, change in the lactate level from induction to chest closure; Change in UMA induction-weaning, change in the UMA level from induction to CPB weaning; Change in UMA weaning-closure, change in the UMA level from CPB weaning to chest closure; Change in UMA induction-closure, change in the UMA level from induction to chest closure; AUC, area under curve; Pauc, P value of the comparison of AUCs between lactate and UMA at each time point. pediatric cardiac surgery in some studies (Durward et al 2005;Murray et al 2007), whereas other studies showed that the UMA level offers no additional advantage over the lactate level in predicting surgical outcomes (Cusack et al 2002;Hatherill et al 2003;Rocktaeschel et al 2003). Both of these reports focused on postoperative or critically ill patients in the ICU.…”
Section: Fig 3 Periopetraive Hemodynamic Variables In the Mae Groupmentioning
confidence: 99%
“…Another report suggests that an elevated strong ion gap is superior to lactate levels as a predictor of mortality after cardiac surgery (Durward et al 2005). However, some reports have questioned the role of the UMA level as a predictor of outcome in critically ill patients (Cusack et al 2002;Hatherill et al 2003;Rocktaeschel et al 2003).…”
mentioning
confidence: 99%
“…Several studies have shown conflicting results regarding the sensitivity and specificity of AG when investigating metabolic acidosis 1, 5, 25, 26, 27. In critically ill foals, a moderate correlation was demonstrated between AG and plasma [ l ‐lac − ], with AG having a good sensitivity (77%) and specificity (83%) in detection of hyperlactatemia > 5 mmol/L 1.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of hyper‐ l ‐lactatemia is considered an accurate predictor of mortality in neonatal and adult humans, horses, and cattle 1, 3, 23, 24, 25, 26. Although recent studies have shown that serial measurement of plasma concentration of l ‐lactate ([ l ‐lac − ]) or measurement of [ l ‐lac − ] clearance might enable more accurate prognostication,3, 4 [ l ‐lac − ] determination at hospital admission are commonly used as a prognostic indicator.…”
mentioning
confidence: 99%
See 1 more Smart Citation